Knowledge and appropriation of information and communication technologies (ICTs) in teacher education - Díaz Pinzón, Jorge Enrique (Universidad de La Salle. Revistas. Actualidades Pedagógicas., 2017)
In order to establish the degree of use and appropriation of information and communication technologies (ICTs) in the competencies of basic and secondary education teachers in 2016, a closed-question survey was applied to a sample of 100 teachers in the municipality of Soacha (Cundinamarca, Colombia). Six survey questions related to a training workshop were analyzed, and six research hypotheses were examined; information was processed using the SPSS statistical package, version 23.0, with a chisquare test for each hypothesis. The correlational analysis of the use and appropriation of ICTs by teachers showed that there is no relationship between the teachers’ work day and the contents of the “Colombia Aprende” webpage, PhET laboratories, resource banks, motivation to implement digital resources, and the possession and appropriate use of tablets. In addition, a weak relationship was evidenced between the work hours of teachers and contents viewed.